Kajian Beberapa Jamur Entomopatogenik pada Ulat Daun Kubis Hijau, Plutella xylostella - Tri Harjaka; Suryanti Suryanti (Jurnal Perlindungan Tanaman Indonesia, 2002)
The use of entomopathogenic fungi for controlling Diamond Back Moth (DBM), Plutella xylostella L. still limited. Even though there are some entomopathogenic fungi could infect DBM. The aim of this research is to know the kind of entomopatogenic fungi on DBM to be used as biological control agent. Some isolates of  fungi were collected  from DBM infected by  the fungi  on field  in Central Java and  Yogyakarta. Fungi infecting DBM was  isolated, and cultured on Potato Dextrose Agar (PDA). Purification, identification and  infection tests were done to know  the potency of each fungal isolates. The results showed thatfive species of fungi infecting DBM, are Beauveria bassiana, Metarhizium anisopliae, Paecilomyces sp. Entomophthora sp.and Hirsutella sp.